EHL oil film thickness under rolling-sliding contact - Nuruzzaman, DM; Sheikh, MAA (Journal of Mechanical Engineering, 2008)
The Elastohydrodynamic lubrication (EHL) minimum oil film thickness is theoretically investigated under rolling with sliding contact. The effects of contact pressure, rolling speed and slip ratio on the EHL minimum oil film thickness are calculated numerically. It is found that for a range of contact pressure from 0.5 to 3.5 GPa, the minimum oil film thickness gradually decreases with the increase in contact pressure. As the rolling speed increases from 3500 to 4500 rpm, oil film thickness is increased. It is also found that the oil film thickness is not much influenced by the slip ratio. Keywords: EHL oil film thickness, Contact pressure, Rolling speed, Slip ratio. DOI: 10.3329/jme.v38i0.902 Journal of Mechanical Engineering Vol.38 Dec. 2007 pp.58-60